1998
DOI: 10.1159/000030958
|View full text |Cite
|
Sign up to set email alerts
|

RHD Gene Polymorphisms among RhD-Negative Chinese in Taiwan

Abstract: Background and Objective: The rare occurrence of anti-D-associated hemolytic disease of the newborn among Chinese is attributable in part to the existence of the weak D phenotype Del among apparently RhD-negative individuals. While exciting advances in the molecular genetics of the Rh blood group have been noted in recent years, the genomic structure of the Del phenotype has seldom been studied in the literature. We try to explore the genomic structure of the RhD gene among apparently Rh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 16 publications
2
44
0
1
Order By: Relevance
“…4). We cannot exclude the possibility that some of the seven remaining alleles have been observed previously [18,19,20,21,22,24,25,26]. Because of the limited published data for those observations, we found more than one "compatible" allele in our study for each previous observation.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…4). We cannot exclude the possibility that some of the seven remaining alleles have been observed previously [18,19,20,21,22,24,25,26]. Because of the limited published data for those observations, we found more than one "compatible" allele in our study for each previous observation.…”
Section: Resultsmentioning
confidence: 63%
“…Apart from a probably lower absolute frequency, we detected in Europeans many parallels to oriental populations: Both populations shared the diverse nature of RHD haplotypes of the first group (probable RHD/CE hybrids) [18,19,20], the preferential occurrence of RHD positive antigen D negative alleles in Cde haplotypes [18], and the comparatively frequent observation of D el phenotypes [19]. In contrast, RHDψ and Cde s are predominant in African populations [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular studies have shown that a heterogeneous array of variant RHD alleles can result in the DEL phenotype [10,18,19,20,21,22,23]. DEL derives from several mechanisms, including splice-site mutation, missense mutation, RHD-CE-D hybrid, frame shift mutation, and a long deletion of the RHD gene [14,24,25,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Between 10 and 33% of Japanese, Chinese, and Korean red cell samples shown to be D − by conventional serological techniques were found to be DEL [116,134,135,258] . Between 10 and 33% of Japanese, Chinese, and Korean red cell samples shown to be D − by conventional serological techniques were found to be DEL [116,134,135,258] .…”
Section: Delmentioning
confidence: 99%